Effect of cyclic irrigation using moderately saline and non‐saline water on onion (Allium cepa L.) yield and soil salinization in semi‐arid areas of Northern Ethiopia. (9th July 2020) - Yohannes, Degol Fissahaye; Ritsema, Coen J.; Habtu, Solomon; Van Dam, Jos C.; Froebrich, Jochen
Abstract: Due to the scarcity and/or unreliability of canal water supply, seepage water is haphazardly used for sole irrigation or in conjunction with canal water in most small‐scale irrigation schemes in northern Ethiopia. This has been a major cause of low crop yield and has aggravated soil salinization. The problem is more exacerbated for onion, which is the major irrigated vegetable crop and is sensitive to salinity. Thus, it is essential to assess a sustainable way to use both water resources conjunctively for the production of onion. A new study in the Ethiopian context was conducted to evaluate the effect of cyclic irrigation using non‐saline canal water (EC, 0.41–0.78 dS m −1 ) and moderately saline seepage water (EC, 0.82–2.19 dS m −1 ) on onion yield and soil salinization for two seasons (2014/2015 and 2015/2016) in the Gumselassa irrigation scheme, Ethiopia. Four irrigation water treatments were applied with three replications consisting of: C (canal), S (seepage), 2CS (two canal and seepage) and CS (canal and seepage). In both seasons, the onion bulb yield variations between the C, 2CS and CS treatments were not significant; however, the S treatment reduced the onion yield significantly compared to all but CS in 2015/2016. The S treatment resulted in significant salt accumulation in the upper soil profile (0–20 cm). The alternate (C : S) cyclic option is thus recommended for alleviation of the problem of freshwater scarcity, without undue onion yield reduction and soil salinization in Gumselassa and similar irrigation schemes. Résumé: En raison de la rareté et/ou du manque de fiabilité de l'approvisionnement en eau du canal, l'eau d'infiltration est utilisée au hasard pour l'irrigation exclusive ou conjointement avec l'eau du canal dans la plupart des petits périmètres irrigués du nord de l'Éthiopie. Cela a été une cause majeure de faible rendement des cultures et d'aggravation de la salinisation des sols. Le problème est plus exacerbé pour l'oignon, qui est la principale culture légumière irriguée et sensible à la salinité. Ainsi, il est essentiel d'évaluer une manière durable d'utiliser conjointement les deux ressources en eau pour la production d'oignons. Une nouvelle étude dans le contexte éthiopien a été menée pour évaluer l'effet de l'irrigation cyclique à l'aide d'eau de canal non saline (EC, 0.41–0.78 dS m −1 ) et d'eau d'infiltration modérément saline (EC, 0.82–2.19 dS m −1 ) sur rendement en oignons et salinisation du sol pendant deux saisons (2014/2015 et 2015/2016) dans le périmètre irrigué de Gumselassa, Ethiopie. Quatre traitements de l'eau d'irrigation ont été appliqués avec trois répétitions comprenant: C (canal), S (infiltration), 2CS (deux canaux et infiltration) et CS (canal et infiltration). Au cours des deux saisons, les variations de rendement du bulbe d'oignon entre les traitements C, 2CS et CS n'étaient pas significatives, mais le traitement S a réduit le rendement d'oignon de manière significative par rapport à tous sauf CS en 2015/2016. Le traitement S a entraîné une accumulation importante de sel dans le profil supérieur du sol (0–20 cm). L'option cyclique alternative (C : S) est donc recommandée pour atténuer le problème de la rareté de l'eau douce, sans réduction excessive du rendement en oignons et salinisation du sol à Gumselassa et dans des périmètres d'irrigation similaires.